Pengembangan Media Pembelajaran pada Kompetensi Dasar Membaca Gambar Menerapkan Sistem Koordinat Berbasis Adobe Flash - Rika Dewi Indriyani; Tiwan Tiwan; Dwi Rahdiyanta (Department of Mechanical Engineering Education, 2017)
This research aimed to design and assess the feasibility of Adobe Flash aided learning media for CNC Turning subject, specifically for the coordinate system topic. The research was a research and development study using the Four-D models of development. Four-D model consists of 4 steps, namely define, design, develop, and disseminate. The instrument being used on this research was closed questionnaires with 4 choices Likert scale. The questionnaires were validated by expert evaluation. Data were collected from the 32 respondents. Data, which were quantitative and qualitative, were analyzed using descriptive analysis technique. The result shows that the learning media meets the teachers' and students' needs and expectation. For the feasibility level, the contents expert gave an average score of 3.37 which can be categorized as